اهتمامات وسائل الإعلام الدولية بقضايا دول العالم الثالث - مقاربة نظرية- - خضير رشيد (جامعة الوادي - University of Eloued, 2021)
تتناول هذه الدراسة الإعلام الدولي وأهميته في ظل تتطور وسائل الإعلام والانتشار الواسع لاستخدامها من قبل الجمهور؛ حيث أصبحت وسائل الإعلام الدولي تقوم بدور في تشكيل الرأي العام الوطني والدولي. وتركز الدراسة على اهتمامات وسائل الإعلام الدولي في تغطيتها للأحداث على قضايا معينة، السياسية منها والإنسانية وقضايا الإرهاب، حيث تقوم وكالات الأنباء بدور بارز في هذه التغطية التي لاقت انتقادات شديدة. Abstract: This study deals with the international media and their importance in light of the development of the media and the widespread use of it by the public. As the international media played a role in shaping national and international public opinion. The study focuses on the interests of the international media in their coverage of events on specific political, humanitarian and terrorism issues, as news agencies play a prominent role in this highly criticized coverage.
International Media And Its Interest On Issues Of Third World Countries- Theoretical Approach
مقال
Keywords: وسائل الإعلام الدولية، الاتصال الدولي، دول العالم الثالث، اهتمامات; International Media, International Communication, Third World Countries, Interests.